(untitled) (Academia Journal of Medicine, 2021)
Background: CKD is characterized by progressive and ongoing loss of kidney function of not <3 months duration with or without decrease in glomerular filtration rate (GFR). CKD leads to increase in blood urea and serum creatinine levels. The present study was conducted to assess the utility of Carbamylated Hemoglobin in determining the overall adequacy of Hemodialysis. Subjects & Methods: 25 patients with chronic kidney disease divided into two groups and one healthy control group. Carbamylated Hemoglobin (CHb) checked at 0 and at 3 months. Kt/V assessed at 0 and 3 months and average Kt/V was calculated. Results: There was non- significant difference in Kt/V, Valine hydantoin absorbance at 570 nm, CHb (ug/gm Hb) and blood flow rate (ml/min) at 8 hours and 12 hours (P> 0.05). The regression equation at 3 months is CHb. = 482.33 + 0.122 age (Yrs) – 0.492 gender + 0.192 duration(months) - 0.624 HD frequency/wks(Hrs) - 0.207 HD vintage(months) + 0.063 BMI + 6.021 Hb.(gm%) + 0.011 BUL(mg/dl) – 0.191 Creatinine(mg/dl) + 0.123 Na(mmol/l) – 1.047 K(mmol/l) + 5.642 Alb.(gm/dl) – 55.12 pH + 0.903 HCO3 - 0.018 iPTH(pg/ml) – 11.54 Kt/V – 96.54 Valine hydantoin absorbance + 0.005 Blood Flow Rate (ml/min). Conclusion: Carbamylated haemoglobin had a direct correlation with blood urea nitrogen levels and with serum creatinine levels in chronic kidney disease patients on maintenance haemodialysis.